Studi Komparasi Muatan Jiwa Pancasila pada Pembelajaran PPKn Kurikulum 2013 dan Kurikulum Merdeka - Alfani, Moch. Farich; Alhan, Anastasya Nida; Septiliana, Lilla (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The era of the current generation Nowadays, students are not fully able to internalize the values of Pancasila in their daily lives. Pancasila values in their daily lives, both in interactions with others and in safeguarding things that are valuable and important to themselves. with others and in maintaining things that are valuable and important for themselves and others. and others. As a result, they often take actions that are not should be in accordance with the rules. The researcher used a systematic literature study systematic literature study using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses). Reviews and Meta Analyses). Data collection was carried out from the results of research research results that have been published in the period 2015 to 2024 on the scale of accredited national journals and reputable international journals. reputable international journals. The results are as follows; Learners can recognize symbols of Pancasila and the Garuda Pancasila State Emblem, and tell the story of the relationship between the symbols of Pancasila and the precepts of Pancasila. the relationship between the symbols of Pancasila and the precepts in Pancasila.